Racial and Economic Factors in Attitudes to Immigration - Christian Dustmann; Ian Preston (Institute for the Study of Labor (IZA), 2000)
Hostility towards minorities may sometimes have economic rather than racial motives. Labour market fears, or concerns about the welfare system, are often believed to manifest themselves in hostile attitudes towards population groups that are considered to be competitors for these resources. The question of how attitudes of majority populations towards immigration are determined is of great importance for implementing appropriate policies. We try to separate racial and economic components to such attitudes. Our analysis is based on the British Social Attitudes Survey, which includes questions on attitudes towards immigration from different minority groups, as well as attitudes towards related concerns, like job security and benefit expenditures. We specify and estimate a multiple factor model. The correlation between answers to questions on immigration and on related issues helps us separate different aspects to attitudes. We find that racial attitudes are strongly associated with hostility to immigration from ethnically distinct populations. Furthermore, there is evidence that welfare and labour market concerns are related to attitudes to immigration, but only among skilled and highly educated workers.
Keywords: J15; F22; 330; Immigration; attitudes; minorities; labour market; welfare; Migranten; Ethnische Gruppe; Diskriminierung; Öffentliche Meinung; Arbeitslosigkeit; Schätzung; Großbritannien